Assessing the efficacy of investigative interviewing training courses: A systematic review. (March 2021) - Akca, Davut; Larivière, Cassandre Dion; Eastwood, Joseph
Substantial resources have been dedicated to designing and implementing training courses that focus on enhancing the interviewing skills of police officers. Laboratory research studies and real-world assessments of the effectiveness of interview training courses, however, have found notably mixed results. In this article, empirical studies ( N = 30) that have assessed the effectiveness of police interview and interrogation training courses were systematically reviewed. We found a wide variation in terms of the type, length, and content of the training courses, the performance criteria used to assess the training effectiveness, and the impact of the training courses on interviewing performance. Overall, the studies found that basic interviewing skills can be developed to a certain level through even short evidence-based training courses. More cognitively demanding skills, such as question selection and meaningful rapport-building, showed less of an improvement post training. The courses that included multiple training sessions showed the most consistent impact on interviewing behavior. This review also indicated a need for more systematic research on training effectiveness with more uniform and longer-term measures of effectiveness. Our findings should help guide future research on this specific topic and inform the training strategies of law enforcement and other investigatory organizations.